2015
DOI: 10.29333/ejecs/20
|View full text |Cite
|
Sign up to set email alerts
|

Survival Tactics of Waste Paper Pickers in Istanbul

Abstract: This study examines migration, ethnicity, stratification, and the informal economy by focusing on Waste Paper Pickers (WPPs) as an informal occupational group in Istanbul. I conducted a yearlong fieldwork project among WPPs in Istanbul, collecting ethnographic, observational, participant observational and interview data to develop a description of the everyday lives of WPPs and how they organize their daily work routines. This paper identified most WPPs as immigrants enmeshed in family, friend and compatriot r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Contemporary ethnographies continue to evidence the social implications of handling dirt for identity formation ( Morales and Lambert 2013 ; Sanders 2010 ). Waste pickers tend to be immigrants, marginalized, “unskilled,” and lower-class laborers ( Yigit 2015 ). The dirty touch required for waste picking can be unpleasant, dirty, and dangerous (e.g., inhalation of dust—UK Health and Safety Executive 2020 ), and this can make it an undesirable occupation.…”
Section: Tactile Historiesmentioning
confidence: 99%
“…Contemporary ethnographies continue to evidence the social implications of handling dirt for identity formation ( Morales and Lambert 2013 ; Sanders 2010 ). Waste pickers tend to be immigrants, marginalized, “unskilled,” and lower-class laborers ( Yigit 2015 ). The dirty touch required for waste picking can be unpleasant, dirty, and dangerous (e.g., inhalation of dust—UK Health and Safety Executive 2020 ), and this can make it an undesirable occupation.…”
Section: Tactile Historiesmentioning
confidence: 99%
“…Mitchell (2009) observed waste intermediaries in Hanoi, examining the effects of the economic restructuring of Vietnam on its informal activity. Yigit (2015) conducted a 1-year ethnography of waste paper pickers in Istanbul, examining the reasons why this type of economic activity continued across generations and demonstrating that waste pickers’ behavior varies by how they work and what they extract for recycling. Whitson (2007, 2011) demonstrated that defining waste picking as an activity that adds no value to the refuse management system further marginalizes informal recyclers in Buenos Aires, Argentina.…”
Section: Studying Informal Waste Pickers: Informal Approaches To Garbmentioning
confidence: 99%
“…Due to their lack of resources, garbage lines the streets of many cities in developing countries. Yigit (2015) asserts that recycling enables waste pickers and their families to survive and benefits communities, municipalities, and the environment. Hence, the state should recognize and value waste pickers in its policy formulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, Yang et al (2017) argue that the recycling methods employed cause environmental pollution and health problems. Yigit (2015) notes that waste pickers benefit themselves, their communities, and local government. Ma et al (2017) note, "In many countries, the informal sector is regarded as undesirable and often a nuisance despite the services it provides."…”
Section: Introductionmentioning
confidence: 99%